Social and ecological influences on human coexistence with gray wolves - Shawn J. Riley; Kenneth F. Kellner; Megan Cross; Emily F. Pomeranz; Jerrold L. Belant (Conservation Science and Practice, 2025)
Abstract We assessed public attitudes toward gray wolves (Canis lupus) in Michigan's Upper Peninsula, focusing on how perceived risks, habitat suitability as a proxy for probability of human–wolf interactions, and socio‐cultural factors affected societal acceptance of wolf populations. A survey (n = 883; response rate = 26.9%) revealed 61.7% of respondents favored reducing wolf abundance, driven primarily by concerns over risks to livestock, white‐tailed deer (Odocoileus virginianus), and human safety. Conversely, those who valued the ecological role of wolves were less inclined to support population reductions. Perceived risks, particularly to deer, strongly influenced attitudes. Wolf habitat suitability correlated with a greater desire for population reduction. Our predictive model, incorporating perceived risks and habitat suitability, demonstrated high accuracy (area under the curve = 0.94). Findings in the context of other research on human–wolf interactions suggest wolf management will be more effective if it addresses specific local concerns, such as deer and livestock, and employs continuous public engagement. Public engagement, especially in rural areas, is essential to build trust and improve understanding of wolf conservation. Integrating local concerns into broader policy and management strategies can foster coexistence and reduce conflicts, ultimately supporting wolf conservation and community well‐being.